Acercamiento antropológico del concepto de salud mental en los aymaras del sector Isluga - Isabel Cuadro Leiva Valdés (Revista Cultura & Religión, 2008)
During a field trip in the Isluga sector, where a major part of the Aymara population of the Tarapacá Region originated, concepts and ritual healings were identified. Western medicine would see this asa mental illness. This observation is done through Anthropology.